2020
DOI: 10.3390/ijms21218322
|View full text |Cite
|
Sign up to set email alerts
|

LINC00973 Induces Proliferation Arrest of Drug-Treated Cancer Cells by Preventing p21 Degradation

Abstract: Overcoming drug resistance of cancer cells is the major challenge in molecular oncology. Here, we demonstrate that long non-coding RNA LINC00973 is up-regulated in normal and cancer cells of different origins upon treatment with different chemotherapeutics. Bioinformatics analysis shows that this is a consequence of DNA damage response pathway activation or mitotic arrest. Knockdown of LINC0973 decreases p21 levels, activates cellular proliferation of cancer cells, and suppresses apoptosis of drug-treated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The role of DDR alterations in colorectal cancer is still not fully studied. There are only a few studies on its clinical impact and no orderly study system has been established ( Chen et al, 2014 ; Lei et al, 2019 ; Sun et al, 2019 ; Karpov et al, 2020 ; Mauri et al, 2020 ; Scagliarini et al, 2020 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of DDR alterations in colorectal cancer is still not fully studied. There are only a few studies on its clinical impact and no orderly study system has been established ( Chen et al, 2014 ; Lei et al, 2019 ; Sun et al, 2019 ; Karpov et al, 2020 ; Mauri et al, 2020 ; Scagliarini et al, 2020 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are few reports on miR-7109-3p. One study highlights LINC00973-miR-7109-Siglec-15 function in the immune evasion of clear-cell renal cell carcinoma [26]. Nagy discovered miR-4506 was differentially expressed in adenoma compared to normal both in CRC tissue and plasma samples [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, LncRNA KTN1-AS1, CASC9, ABHD11-AS1, LINC00467 could participate in the progress of NSCLC ( 20 23 ). Studies have reported that LINC00973 was related to cancer progression ( 18 , 19 , 24 , 25 ). The expression level of LINC00973 was upregulated in cetuximab-resistant colorectal cancer H508/CR cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chemotherapy could upregulate the expression level of LINC00973 in normal cells and cancer cells, which might be related to the activation of DNA damage response pathways or mitotic arrest. LINC00973 could reduce p21 levels, activate cancer cell proliferation, and reduce the lethality of drugs ( 18 ). Siglec-15 was a tumor immunosuppressive molecule.…”
Section: Introductionmentioning
confidence: 99%